Developing a proof of principle 3D-printed lab-on-a-disc assay platform. - Tothill, Alexander M. (Cranfield University, 2017)
A 3D-printed microfluidic lab-on-a-disc (LOAD) device was designed and manufactured using a low cost (˜£1600) consumer grade fused deposition modelling (FDM) Ultimaker 2+ 3D printer with imbedded microfluidic channels 1 mm wide, 400 μm depth and with a volumetric capacity of approximate 23 μl. FDM printers are not typically used, or are capable, of producing the fine detailed structures required for microfluidic fabrication; in addition 3D-printed objects can suffer from poor optical transparency. However, in this work, imbedded microfluidic channels were produced and the optical transparency of the device was improved though manufacture optimisation to such a point that optical colourimetric assays can be performed in a microfluidic cuvette device with sample path length of 500 μm and volumetric capacity of 190 μl. When acetone vapour treatment was used, it was possible to improve transparency of plastic samples by up to a further 30%. The LOAD device is capable of being spun using an unmodified optical disc drive (ODD), demonstrating the centrifugation based separation of plasma from whole blood in a low-cost FDM 3D-printed microfluidic LOAD device. A cholesterol assay and glucose assay was developed and optimised using cholesterol oxidase (ChOx) or glucose oxidase (GlOx) respectively and horseradish peroxidase (HRP) for the oxidative coupling of chromotropic acid (CTA) and 4-aminoantipyrine (AAP). This produced a blue quinoneimine dye with a broad absorbance peaking at 590 nm for the quantification of cholesterol/glucose in solution. The colourimetric enzymatic cascade assays were developed for use within low-cost FDM 3D-printed microfluidic devices to demonstrate the capabilities and functionality of the devices. For comparison, the assay was run in standard 96 well plates with a commercial plate reader. The results demonstrated that the quantification of 0-10 mM glucose solution using a 3D-printed microfluidic optical device had a performance comparable to a plate reader assay; glucose assay in whole blood samples R² = 0.96.
Keywords: 3D-Printing; Microfluidics; Devices; Glucose; Enzymatic; Low cost; whole blood